Genetic and physiological bases for variation in water use efficiency in canola. (14th August 2020) - Raman, Harsh; Raman, Rosy; McVittie, Brett; Borg, Lauren; Diffey, Simon; Singh Yadav, Avilash; Balasubramanian, Sureshkumar; Farquhar, Graham
Abstract: Drought stress due to water deficiency threatens production of canola worldwide. Carbon isotope discrimination (Δ 13 C), a trait that can be used to assess efficient water use, provides an opportunity to exploit natural variation in canola for stable production. Here, we show that substantial genetically controlled phenotypic variation in water use efficiency (WUE) component trait, Δ 13 C (20.4 to 23.6‰) exists among accessions of canola. Quantitative trait loci (QTL) analysis revealed ten loci for Δ 13 C, each accounting for 2.5% to 16.5% of the genotypic variation. One of the significant QTL for Δ 13 C was co‐localized with a QTL for flowering time, a trait implicated in drought escape and was mapped in the vicinity of the FLOWERING LOCUS T (FT) on chromosome A07. Gene expression analyses revealed that among FT paralogs, BnC6.FTb expression was significantly correlated ( r = 0.33, p < .01) with variation in Δ 13 C across at least two environments in a canola DH population. Integration of data based on instantaneous single leaf gas exchange, dry matter Δ 13 C, and whole plant measurements suggests a possible trade‐off between early flowering and WUE. Our findings provide insights into the complexity of Δ 13 C and WUE which could enable the development of canola varieties resilient to drought and increasing canola productivity under water‐limited conditions. Abstract : We show that substantial genetically controlled variation in Δ13C exists in canola. At least two genomic regions underlying Δ13C variation were located near loci for flowering time and other plant development traits. Integration of data based on intrinsic WUE, Δ13C, and seed yield measurements suggests a possible trade‐off between early flowering and WUE in drought stressed environments.